The Role of Competition Law in Protecting MSMEs from Predatory Pricing Practices in E-Commerce Platforms - Rahmi Zubaedah; Rani Apriani; Pamungkas Satya Putra (Faculty of Law, Universitas Pekalongan, 2025)
The research explores the impact of predatory pricing practices by foreign businesses on e-commerce platforms, which pose significant challenges to Micro, Small, and Medium Enterprises (MSMEs) in Karawang, Indonesia. Using a normative legal research approach, the study evaluates the adequacy of regulations such as Law Number 5 of 1999 on Prohibition of Monopolistic Practices and Unfair Business Competition and Ministry of Trade Regulation Number 50 of 2020 in providing legal protection to MSMEs. The study highlights the role of the Business Competition Supervisory Commission (KPPU) in monitoring and enforcing fair competition laws within the digital marketplace. The findings reveal that imported products sold at significantly low prices undermine local MSMEs’ competitiveness, exacerbating the challenges they face in the digital economy. Although government initiatives such as prioritizing domestic products, implementing stricter regulations, and launching campaigns like the